Beyond Eurocentric Models: Rethinking Guidance and Counseling Services in Tanzanian Schools Through an Indigenous Lens - Almasi, Mustapha; H. Kimangale, Saldin; Kessy, Neema (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Guidance and counselling in schools are key helping children cope, maintain their mental health and continue learning.  However, Western psychological approaches have dominated counselling services in Tanzania making students and counsellors as mere consumers. This might hinder the educational and growth needs of a Tanzanian child. Therefore, this paper reports a review of literature in Tanzania to investigate provision of guidance and counselling services in schools in the light of Afrocentric approach which takes in the Tanzanian cultural context. The paper highlights the historical development of guidance and counselling services in Tanzanian schools, then examines the setbacks of employing Western approaches on providing guidance and counselling services, and finally, advocates the need for Afrocentric approaches as an important aspect in practicing school guidance and counselling in Tanzanian context.